Life Cycle Assessment (LCA): A Tool for Sustainable Development and Environmental Management of Products - Nidhi Gupta; Rohit Singh Lather; Shyam Lal Sharma (International Journal of Industrial and Product Design Engineering, 2024)
Life cycle assessment (LCA) is a crucial technique for clearly understanding how much room there is for product improvement in a given good or service. Because of its high cost and application in eco-design, supply chain management, green buying, sustainable investing, and other relevant activities, manual data engineering and analysis processes. Traditional LCA methodologies and technology may need more scalability regarding substantial product portfolios and expanding reporting requirements. The Sustainability Data Science Life Cycle (S-DSLC) is an idea for workflow automation for multi-purpose LCA of extensive product portfolios. Data Science Life Cycle (DSLC), cross-industry standard methodology for data mining (CRISP-DM), and LCA frameworks are all combined in one concept. The concept's key components include automating data preparation, model generation, and life cycle impact assessment using modern data analytic tools, as well as deploying LCA to produce interactive browser tools (like LCA dashboards and Guided Analytics) tailored to the requirements of specific roles and business processes. The concept's presentation shows how scalability advantages for managing sizable product portfolios and the extensive use of LCA results in several business processes may be considerable. LCA measures a product's environmental impact at each stage, from production to disposal or recycling. The attainment of improvements for handling extensive product portfolios and widespread implementation of LCA results in different business processes. LCA assesses a product's environmental effect at every stage of its life, from manufacturing through disposal or recycling. LCA seeks to aid in decision-making as well as data generation. For instance, to increase the sustainability of products.
Keywords: Life cycle assessment LCA; Risk assessment; life cycle inventory LCI; product development valuation; strategic environmental assessment